Efforts to stimulate PWMD patients through psychotherapy based on media craft activities - Sri Wahyuningsih; Misnadin Misnadin; Fadia Nur Andini; Safira Uzma Putri V; Fikri Haykal Ardiansyach; Linda Fitro Asmarani; Shinta Nur Afni (Universitas Muhammadiyah Magelang, 2024)
People with mental disorders often face health challenges and are at risk of social isolation, highlighting the importance of appropriate treatment to enhance their quality of life. The objective of this initiative is to improve the quality of life and foster independence among patients with mental disorders (ODGJ) through psychotherapy in the form of handicraft activities. The program is conducted collaboratively by the community service team and the Omben Sampang Community Health Center team. It involves providing hands-on training and direct guidance to ODGJ patients in creating tote bag paintings and shibori batik. As a result of this activity, ODGJ patients exhibit positive developments in both their quality of life and their ability to engage in daily activities independently. These outcomes serve as a foundation for the development of effective treatment programs for individuals with mental disorders.